Mesh cloth composite TPU film and preparation method thereof
By crushing the TPU film into particles and filling it into the mesh hole of the mesh cloth, and tightly bonding it to the mesh cloth after heating, the problem of unstable adhesion between the TPU film and the mesh cloth composite material is solved, and its adhesion stability and overall performance are significantly improved.
Patent Information
- Application Number
- CN202411704291.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing TPU film and mesh composite materials are prone to problems such as unstable adhesion, cracking and peeling during use, which affects its overall performance and service life.
By crushing the TPU film into particles and spraying it into the mesh cloth, it is filled into the mesh hole of the mesh cloth, and melting during the heating process to form a pretreated mesh cloth, and then attaching the TPU film to one side and hot pressing is performed to ensure the close bond between the TPU film and the mesh cloth.
The adhesion stability between the TPU film and the mesh is significantly improved, and the adhesion instability and cracking problems that may occur in traditional methods are avoided, and the overall performance, practicality and service life of the composite material are improved.
Smart Images

Figure BDA0005154157480000051 
Figure BDA0005154157480000052 
Figure BDA0005154157480000061
Abstract
Description
Technical Field
[0001] The present application relates to the field of composite materials, and more specifically, to a mesh composite TPU film and a preparation method thereof. Background Art
[0002] As a high-performance material, TPU film is widely used in the fields of automobiles, electronics, etc. By compounding with mesh, its physical properties, such as wear resistance, tear resistance and flexibility, can be significantly improved. This composite material can not only meet the needs of the high-end market, but also maintain good performance in various harsh environments. However, with the continuous growth of market demand and the requirements of technological progress, how to effectively improve the adhesion stability of composite materials has become one of the key issues that need to be solved urgently.
[0003] At present, in order to achieve effective compounding of TPU film and mesh, commonly used methods include direct bonding, adhesive bonding and hot pressing bonding. Among them, the direct bonding method is to simply bond the TPU film and mesh together, which is easy to operate but has low adhesion strength; the adhesive bonding method is to use a special adhesive to fix the two. Although the adhesion is strong, there are problems such as high cost and poor environmental protection; the hot pressing bonding method is to combine the TPU film and mesh at a certain temperature and pressure. Although it can achieve a good adhesion effect, it is still difficult to completely avoid uneven adhesion and interface separation in actual operation.
[0004] These existing composite methods generally have the problem of unstable adhesion, which causes the composite materials to crack and peel during use, seriously affecting their overall performance and service life. This problem is particularly prominent in applications such as automotive interiors and tires, and a more reliable and stable composite technology is urgently needed to solve these problems. Summary of the invention
[0005] In order to reduce the occurrence of cracking, peeling and the like, and further improve the physical properties of the mesh composite TPU film, the present application provides a mesh composite TPU film and a preparation method thereof.
[0006] In a first aspect, a method for preparing a mesh composite TPU film is prepared by the following method: TPU film: melt-extruding and calendering TPU particles to form a TPU film; Mesh pretreatment: crush the TPU film to obtain TPU particles; then spray the TPU particles into the mesh and fill them into the mesh holes of the mesh, heat to melt the TPU particles, and obtain a pretreated mesh; A TPU film is attached to at least one side of the pretreated mesh, and hot pressed to obtain a mesh composite TPU film.
[0007] The adhesion stability between the TPU film and the mesh can be significantly improved. First, the TPU film is crushed to obtain TPU particles, which are then sprayed into the mesh so that the TPU particles are filled into the mesh holes of the mesh. After heating, the TPU particles melt to form a stable pretreated mesh. This pretreatment method not only enhances the physical properties of the mesh, but also improves the bonding strength between the subsequent TPU film and the mesh. Finally, a TPU film is attached to at least one side of the pretreated mesh and hot pressed to ensure a tight bond between the TPU film and the mesh, effectively avoiding the adhesion instability and cracking problems that may occur in traditional methods, and improving the overall practicality, reliability and physical properties.
[0008] Preferably, the hot pressing temperature is 130-150° C., the hot pressing pressure is 10-30 kg, and the hot pressing time is 0.2-3 s.
[0009] The hot pressing temperature is 130-150°C, the hot pressing pressure is 10-30kg, and the hot pressing time is 0.2-3s, which can ensure the full fusion between the TPU film and the pretreated mesh, improve the adhesion strength and stability of the two, avoid the problem of unstable adhesion in traditional methods, reduce the risk of cracking of the composite material during use, and improve the overall performance and service life of the product.
[0010] Preferably, the TPU film has a gram weight of 120-2000 g / m 2 .
[0011] 120-2000g / m 2 The TPU film can be selected according to different application scenarios, which enhances the application range and flexibility of the product. The thickness of the preferred TPU film is controlled at 180-320g / m 2 Within the range, sufficient mechanical strength can be guaranteed, and the process of the present application can be combined to achieve better physical properties of the mesh composite TPU film.
[0012] Preferably, the TPU particles are modified TPU particles, and the TPU particles are made from the following raw materials in percentage by weight: TPU: 60-80% Catalyst: 0.1-0.3% Bismaleimide derivatives: 3-8% Polyethylene glycol derivatives: 2.7-5.2% The remainder is filler.
[0013] The modified TPU particles can significantly improve the adhesion between the TPU film and the mesh, making the overall performance of the composite material more stable, avoiding problems such as cracking during use, and improving practicality and durability.
[0014] The content of TPU at 60-80% provides basic mechanical strength and elasticity, ensuring the basic performance of the composite material. The catalyst accelerates the chemical reaction, helps the uniform dispersion and melting of TPU particles, and improves the processing performance. It also promotes the further reaction of bismaleimide derivatives, thereby improving the adhesion performance of TPU. Combined with the capacity-enhancing, compatibility and dispersion effects of polyethylene glycol derivatives, it has a synergistic effect with bismaleimide derivatives, enhancing the bonding force between the modified TPU and the mesh, reducing the risk of delamination, and promoting the full mixing of TPU and fillers, improving physical properties, and further improving the uniformity and stability of the mesh composite TPU film, so that it has better durability.
[0015] Preferably, the maleimide derivative is bis(3-ethyl-5-methyl-4-maleimidophenyl)methane and / or N,N'-(4-methyl-1,3-phenylene)bismaleimide.
[0016] The maleimide derivatives are bis(3-ethyl-5-methyl-4-maleimidophenyl)methane and / or N,N'-(4-methyl-1,3-phenylene)bismaleimide, which can effectively improve the adhesion of TPU particles and material properties, make the bond between TPU film and mesh more firm, reduce cracking of composite materials during use, and significantly improve the overall performance and practicality of composite materials.
[0017] Preferably, the maleimide derivative is composed of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane and N,N'-(4-methyl-1,3-phenylene)bismaleimide in a weight ratio of 1:(1.5-3.2).
[0018] The addition of bismaleimide derivatives and polyethylene glycol derivatives effectively improves the adhesion and material properties of TPU materials. Bismaleimide derivatives can chemically react with TPU molecular chains, increase the cross-linking density between molecules, and thus enhance the adhesion between TPU and mesh.
[0019] A specific proportion of maleimide derivatives, the maleimide derivatives are composed of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane and N,N'-(4-methyl-1,3-phenylene)bismaleimide in a weight ratio of 1:(1.5-3.2). The selection of this specific ratio can ensure the adhesion performance while maintaining the mechanical strength and flexibility of the TPU material, and avoid the brittleness of the material due to excessive cross-linking.
[0020] In summary, through the above technical scheme, the adhesion performance between the TPU film and the mesh is significantly improved, the overall stability of the composite material is enhanced, the cracking problems that may occur during use are reduced, and the practicality and durability of the product are improved.
[0021] Preferably, the polyethylene glycol derivative is PEG-40 hydrogenated castor oil and / or polyethylene glycol diacrylate.
[0022] By adopting the above technical scheme, the polyethylene glycol derivative is PEG-40 hydrogenated castor oil and / or polyethylene glycol diacrylate, which can effectively increase the volume, promote compatibility and dispersion, make the TPU particles more uniform during the melting process, improve the mechanical properties and adhesion of the TPU film, and thus enhance the overall performance and stability of the mesh composite TPU film.
[0023] Preferably, the filler is one or more of white carbon black, white graphite, calcium carbonate and glass fiber.
[0024] The above scheme adopts the above technical scheme, and the filler is one or more of white carbon black, white graphite, calcium carbonate and glass fiber, which can significantly improve the mechanical strength and durability of the TPU film and enhance the overall performance of the composite material. Specifically: When white carbon black, white graphite and glass fiber are added, white carbon black has a good reinforcing effect and can effectively improve the tensile strength and tear strength of the TPU film.
[0025] White graphite can improve the thermal conductivity of TPU film, help dissipate heat, and reduce performance degradation caused by high temperature.
[0026] Calcium carbonate as a filler can reduce costs while increasing the hardness and rigidity of the TPU film.
[0027] Glass fiber has excellent mechanical properties and dimensional stability, and can significantly improve the impact resistance and wear resistance of TPU film.
[0028] The combined use of the above fillers enables the final mesh composite TPU film to exhibit better physical properties and longer service life in practical applications.
[0029] Preferably, the particle size of the TPU particles is 1000-2000 mesh, and the melting temperature of the TPU particles is 160-170°C.
[0030] In the above scheme, the particle size of TPU particles is 1000-2000 mesh, which can ensure that the TPU particles are evenly distributed and fully penetrate into the mesh of the mesh, enhance the adhesion between the mesh and the TPU film, and improve the overall strength and stability of the composite material. At the same time, the melting temperature of TPU particles is 160-170℃, so that the TPU particles can melt quickly and tightly combine with the mesh during the subsequent hot pressing process, avoiding problems such as cracking caused by unstable adhesion in traditional processes, and significantly improving the practicality and durability of the product.
[0031] In a second aspect, a mesh composite TPU film comprises a mesh and at least one TPU film layer, wherein the mesh holes of the mesh are filled with TPU material, and the TPU film layer is stably connected to the TPU material and the mesh wire of the mesh. The mesh composite TPU film is prepared by a method for preparing a mesh composite TPU film.
[0032] Mesh composite TPU film has the following effects: Enhanced adhesion stability: By spraying TPU particles into the mesh of the mesh and allowing them to penetrate, and then heating to melt the TPU particles, the adhesion between the mesh and the TPU film is made stronger, avoiding the adhesion instability problem caused by the traditional direct bonding method, and improving the overall performance and durability of the composite material.
[0033] Improved physical properties: The use of modified TPU particles, especially the addition of bismaleimide derivatives and polyethylene glycol derivatives, significantly improves the adhesion and material properties of the TPU film, making the composite material have better mechanical strength and chemical corrosion resistance.
[0034] Optimize the preparation process: By controlling the hot pressing temperature, pressure and time, the good combination of TPU film and mesh is ensured, while the uniformity and consistency of the composite material are guaranteed, the production process is simplified and the production cost is reduced.
[0035] Improve functionality: The selection of fillers, such as white carbon black, white graphite, calcium carbonate and glass fiber, not only enhances the mechanical properties of the composite material, but also gives the material more functional properties, such as conductivity, heat insulation and wear resistance.
[0036] Precise control of particle size and melting point: The particle size of TPU particles is controlled within the range of 1000-2000 mesh, and the melting temperature is set at 160-170°C, ensuring that the TPU particles can effectively penetrate into the mesh of the mesh and melt under appropriate conditions, further enhancing the structural stability of the composite material.
[0037] In summary, the present application includes at least one of the following beneficial technical effects: 1. The TPU film is crushed into TPU particles and sprayed into the mesh, so that the TPU particles are filled into the mesh holes of the mesh. During the heating process, the TPU particles melt and tightly bond with the mesh, which effectively improves the adhesion stability between the mesh and the TPU film, avoiding the problems of weak adhesion and cracking that are prone to occur in traditional methods; 2. The bismaleimide derivatives and polyethylene glycol derivatives in the modified TPU particles significantly improve the adhesion and material properties of the TPU material, making the final composite material have better mechanical strength and durability, and is suitable for application scenarios with high strength requirements; 3. By controlling the hot pressing parameters (such as temperature, pressure and time), the bonding between the TPU film and the pre-treated mesh is ensured to be more uniform and tight, which further enhances the overall performance of the composite material and prolongs its service life. DETAILED DESCRIPTION
[0038] The following embodiments further illustrate the present application in detail.
[0039] Introduction of some raw materials: TPU: Covestro TPU 285 from Germany; Catalyst: Vanadium 2-ethylhexanoate; PEG-40 hydrogenated castor oil: preferably model CO-40 from Jining Tangyi Chemical Co., Ltd.; Polyethylene glycol diacrylate viscosity average molecular weight 600-700; The molecular structure of N,N'-(4-methyl-1,3-phenylene)bismaleimide is as follows: The molecular structure of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane is as follows: The particle size of white carbon black, white graphite and calcium carbonate is 1000 mesh; Glass fiber is short glass fiber with a wire diameter of 10-20 microns and a length of 30-50 microns; The weight range of the TPU film in the present application is preferably 180-320 g / m 2 When applied to large tire treads, the weight can reach 1000-2000g / m 2 The particle size of the TPU particles is 800-4000 mesh, preferably 1000-2000 mesh in the embodiment; the melting temperature of the TPU particles is 150-200°C, preferably 160-170°C in the embodiment; the hot pressing temperature is 130-180°C, preferably 130-150°C in the embodiment.
[0040] Preparation example of modified TPU particles Preparation Example 1 A modified TPU particle is prepared by the following method: According to the weight percentage, 75% TPU, 0.5% catalyst, 8% bismaleimide derivative, 5.2% polyethylene glycol derivative, and 11.2% filler are weighed and put into a stirring device, and stirred at a speed of 200r / min for 10min to fully mix them to obtain a mixture A; the mixture A is heated to 170°C to make it completely melted, and then stirred for 5min and fully mixed, and then the material is put into an extruder for extrusion. The extruded material enters a cooling device to be cooled to 30°C, and then enters a granulator for granulation. The obtained pellets are placed in an oven at 80°C for baking for 10min to obtain modified TPU particles.
[0041] The maleimide derivative is N,N'-(4-methyl-1,3-phenylene)bismaleimide; the polyethylene glycol derivative is PEG-40 hydrogenated castor oil; and the filler is white carbon black.
[0042] Preparation Example 2-3 The difference between Preparation Example 2-2 and Preparation Example 1 is that the amount of raw materials used is different, as shown in Table 1; Table 1 Raw material dosage of preparation examples 1-3 (%) Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 2 is that the maleimide derivative is bis(3-ethyl-5-methyl-4-maleimidophenyl)methane.
[0043] Preparation Example 5 Preparation Example 5 is different from Preparation Example 2 in that the maleimide derivative is prepared from bis(3-ethyl-5-methyl-4-maleimidophenyl)methane and N,N'-(4-methyl-1,3-phenylene)bismaleimide in a weight ratio of 1:1.5.
[0044] Preparation Example 6 Preparation Example 6 is different from Preparation Example 2 in that the maleimide derivative is prepared from bis(3-ethyl-5-methyl-4-maleimidophenyl)methane and N,N'-(4-methyl-1,3-phenylene)bismaleimide in a weight ratio of 1:2.2.
[0045] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 2 and Preparation Example 1 is that the maleimide derivative is composed of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane and N,N'-(4-methyl-1,3-phenylene)bismaleimide in a weight ratio of 1:3.2.
[0046] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 6 is that the polyethylene glycol derivative is polyethylene glycol diacrylate.
[0047] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 6 is that the polyethylene glycol derivative is composed of PEG-40 hydrogenated castor oil and polyethylene glycol diacrylate in a weight ratio of 1:0.3.
[0048] Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 9 is that the filler is white graphite.
[0049] Preparation Example 11 The difference between Preparation Example 11 and Preparation Example 9 is that the filler consists of calcium carbonate and glass fiber in a weight ratio of 1:0.1.
[0050] Preparation Example 12 The difference between Preparation Example 12 and Preparation Example 9 is that the filler is composed of white carbon black, white graphite and glass fiber in a weight ratio of 1:0.1:0.3.
[0051] Preparation Comparative Example Preparation Comparative Example 1 The difference between Preparation Comparative Example 1 and Preparation Example 1 is that an equal amount of the bismaleimide derivative is replaced with TPU.
[0052] Preparation Comparative Example 2 The difference between Preparation Comparative Example 2 and Preparation Example 2 is that an equal amount of the polyethylene glycol derivative is replaced with TPU. Example
[0053] Example 1 A mesh composite TPU film includes a mesh and at least one TPU film layer, preferably two TPU film layers, and the two TPU film layers are respectively arranged on the two sides of the mesh. The mesh holes of the mesh are filled with TPU material, and each TPU film layer is stably connected to the TPU material and the mesh wire of the mesh, so as to obtain a mesh composite TPU film with a stable structure.
[0054] The mesh composite TPU film is prepared by the following method: TPU film: Put TPU particles into a twin-screw extruder for melt extrusion, and then calender them in a calender to form a TPU film; Mesh pretreatment: crush the TPU film to obtain TPU particles; then spray the TPU particles into the mesh and fill them into the mesh holes of the mesh, heat to 160°C for 2 minutes to melt the TPU particles, and obtain a pretreated mesh; TPU films are attached to both sides of the pretreated mesh, and then hot pressed to obtain a mesh composite TPU film. The gram weight of the TPU material is 60% of the gram weight of the mesh.
[0055] Among them, the mesh fabric is nylon cord fabric, which is interwoven with warp and weft threads. Both the warp and weft threads are made of nylon 66 threads with a diameter of 0.2mm. The radial line density is 40 threads / 5cm, and the weft line density is 40 threads / 5cm.
[0056] The weight of each layer of TPU film is 180g / m 2 ; The hot pressing temperature is 130℃, the hot pressing pressure is 30kg, and the hot pressing time is 3s.
[0057] The particle size of the TPU microparticles is 1000 mesh, and the melting temperature of the TPU microparticles is 170°C.
[0058] Example 2 The difference between Example 2 and Example 1 is that the process parameters are different, as follows: The weight of each layer of TPU film is 260g / m 2 ; The hot pressing temperature is 140℃, the hot pressing pressure is 20kg, and the hot pressing time is 1.5s.
[0059] The particle size of the TPU microparticles is 1500 mesh, and the melting temperature of the TPU microparticles is 160°C.
[0060] Example 3 The difference between Example 3 and Example 1 is that the process parameters are different, as follows: The weight of each layer of TPU film is 320g / m 2 The hot pressing temperature is 150°C, the hot pressing pressure is 10kg, and the hot pressing time is 0.2s.
[0061] The particle size of the TPU microparticles is 2000 mesh, and the melting temperature of the TPU microparticles is 160°C.
[0062] Example 4-17 The difference between Example 4-17 and Example 2 is that: TPU is a modified TPU, as shown in Table 2; Table 2 Sources of modified TPU of Examples 4-17 Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that there is no TPU material inside the mesh. The specific process is as follows: TPU film: TPU particles are put into a twin-screw extruder for melt extrusion, and then calendered in a calender to form a TPU film; TPU films are attached to both sides of the mesh, and then hot pressed to obtain a mesh composite TPU film.
[0063] The weight of each layer of TPU film is 180g / m 2 +1 / 2 the weight of TPU material.
[0064] Performance testing Detection method / test method The mesh composite TPU films obtained in Examples 1-17 and Comparative Example 1 were subjected to the following performance tests: Peeling force test: refer to GB / T 2792-1998, fix one side of the cloth composite TPU film completely, cut a 1mm incision on the other side with a knife to separate the TPU film layer from the mesh, and then test the force used to peel off the TPU film layer. Repeat the above test 3 times and take the average value.
[0065] Breaking strength: The breaking strength of the microfiber fabrics obtained in Examples 1-17 and Comparative Example 1 was tested with reference to GB / T3923.1-1997.
[0066] The above experimental data are detailed in Table 3; Table 3 Experimental data of Examples 1-17 and Comparative Example 1 Combining Example 1 and Comparative Example 1 and Table 3, it can be seen that the peeling force of Example 1 is 1.54 kg higher than that of Comparative Example 1, and the breaking strength of Example 1 is 4.7 kg higher than that of Comparative Example 1, indicating that the preparation process of the present application can enable the layer structure of the mesh composite TPU film to obtain better stability, reduce the occurrence of cracks, and also have better breaking strength, reducing the possibility of damage.
[0067] Combining Example 2 and Example 4 with Table 3, it can be seen that the peel force and breaking strength of Example 1 are greater than the peel force and breaking strength of Example 2, indicating that the modified TPU obtained by the preparation method of the present application has a better adhesion effect, so that the layer structure of the mesh composite TPU film is stably connected, and has better physical properties, thereby improving the practicality of the mesh composite TPU film.
[0068] By comparing Example 5 and Examples 8-10, and combining with Tables 2-3, it can be seen that the peeling force and breaking strength of the mesh composite film obtained by Examples 8-10 using Preparation Examples 5-7 are higher than those of Example 5, indicating that the compounding of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane and N,N'-(4-methyl-1,3-phenylene)bismaleimide plays a synergistic role and further enhances the comprehensive performance of the mesh composite film.
[0069] By comparing Examples 16-17 with Example 4 and combining with Tables 2-3, it can be seen that the peeling force and breaking strength of Examples 16-17 are lower than the peeling force and breaking strength of Example 4, indicating that the present application further enhances the comprehensive performance of the mesh composite TPU film by compounding bismaleimide derivatives and polyethylene glycol derivatives and modifying TPU.
[0070] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a mesh composite TPU film, characterized in that: Prepared by the following method: TPU film: TPU particles are melt-extruded and calendered to form a TPU film; Mesh pretreatment: crush the TPU film to obtain TPU particles; Then, the TPU particles are sprayed into the mesh and filled into the mesh holes of the mesh, and the TPU particles are heated to melt to obtain a pretreated mesh; A TPU film is attached to at least one side of the pretreated mesh, and hot pressed to obtain a mesh composite TPU film.
2. The method for preparing a mesh composite TPU film according to claim 1, characterized in that: The hot pressing temperature is 130-180° C., the hot pressing pressure is 10-30 kg, and the hot pressing time is 0.2-3 s.
3. The method for preparing a mesh composite TPU film according to claim 1, characterized in that: The TPU film has a grammage of 120-2000 g / m 2 .
4. The method for preparing a mesh composite TPU film according to claim 1, characterized in that: The particle size of the TPU particles is 800-4000 meshes, and the melting temperature of the TPU particles is 150-200°C.
5. The method for preparing a mesh composite TPU film according to claim 1, characterized in that: The TPU particles are modified TPU particles, and the TPU particles are made from the following raw materials in weight percentage: TPU: 75-90% Catalyst: 0.1-0.5% Bismaleimide derivatives: 3-8% Polyethylene glycol derivatives: 2.7-5.2% The remainder is filler.
6. The method for preparing a mesh composite TPU film according to claim 5, characterized in that: The maleimide derivative is bis(3-ethyl-5-methyl-4-maleimidophenyl)methane and / or N,N'-(4-methyl-1,3-phenylene)bismaleimide.
7. The method for preparing a mesh composite TPU film according to claim 6, characterized in that: The maleimide derivative is composed of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane and N,N'-(4-methyl-1,3-phenylene)bismaleimide in a weight ratio of 1:(1.5-3.2).
8. The method for preparing a mesh composite TPU film according to claim 5, characterized in that: The polyethylene glycol derivative is PEG-40 hydrogenated castor oil and / or polyethylene glycol diacrylate.
9. The method for preparing a mesh composite TPU film according to claim 5, characterized in that: The filler is one or more of white carbon black, white graphite, calcium carbonate and glass fiber.
10. A mesh composite TPU film, characterized in that: The invention comprises a mesh and at least one TPU film layer, wherein the mesh holes of the mesh are filled with TPU material, and the TPU film layer is stably connected with the warp and weft of the TPU material and the mesh, and a preparation method of a mesh composite TPU film according to any one of claims 1 to 9.
Citation Information
Patent Citations
TPU clad net
CN101225610A
A high-adhesion, airtight TPU coated fabric and its preparation method
CN102285185A
Halogen-free flame-retardant functional polyurethane sealant and preparation process thereof
CN117363298A
Cited By
TPU (thermoplastic polyurethane) mesh fabric production process and TPU mesh fabric production equipment
CN120792116A
TPU mesh fabric production process and production equipment
CN120792116B